Dare to care : a philosophical discussion about the virtue of courage among care home managers - Calvert, Anita (Array, 2019)
Paper is divided into two parts. The first contains two philosophical discussions about comprehension of courage and the second focuses on the findings in an empirical study with care home managers about the virtue of courage. First discussion revolves around the question whether the virtue of courage is expressed a) only in life–threatening situations or is it a virtue trained and exemplified in b) everyday life settings, while the second emphasises the difference between i) courage of efficiency as a skill and ii) courage of excellence as a virtue. Arguments here support a vision of courage as the virtue of excellence expressed in everyday life settings. The second part of the paper highlights a new perspective of courage with regards to the notion of care towards the aim of the courageous endeavour. The ‘courage of care’ supports the idea that the courage practised as the virtue of excellence aims to develop the moral character of the actor fundamentally outside of the life–threatening situation. Care for the self, other people, animals and intangible moral principles inspire us to do brave deeds. Thus, by accepting Alasdair MacIntyre’s statements that a) in the times of the peace managers represent moral idols and b) idea that the notion of courage should be closely related to the practice of care and compassion, the research continued with the interviews with the care home managers in Kent county in England. Conversations with care home managers released further insights into how care and compassion influence the understanding of the virtue of courage.